Problems of the coming decade - Yasusuke Murakami (Intereconomics, 1976)
In the last issue of INTERECONOMICS Willis W. Harman and Bernard Cazes explained their views of the basic political, economic, and social problems which the USA and Europe, respectively, will face in the 1980s. The following article which is also an excerpt from the author's report to the Second International Symposium on New Problems of Advanced Societies, held from May 3 to 7, in Hamburg, deals with the Japanese Problems against the background of decelerating growth.
Keywords: 330; Japan